Resolution threats and bank discipline: What Europe can learn for the Single Resolution Mechanism from US experience - Magdalena Ignatowski; Josef Korte (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
Can a tightening of the bank resolution regime lead to more prudent bank behavior? This policy paper reviews arguments for why this could be the case and presents evidence linking changes in bank resolution regimes with bank risk-taking. The authors find that the tightening of bank resolution in the U.S. (i.e., the introduction of the Orderly Liquidation Authority) significantly decreased overall risk-taking of the most affected banks. This effect, however, does not hold for the largest and most systemically important banks - too-big-to-fail seems to be unresolved. Building on the insights from the U.S. experience, the authors derive principles for effective resolution regimes and evaluate the emerging resolution regime for Europe.
urn:nbn:de:hebis:30:3-356787
Keywords: 330; risk-taking; bank resolution regimes; USA; Europe